Tradisi Sekaten dalam Pandangan Santri Milenial : Studi Kasus di Pondok Pesantren Darul Qura’an Wal Irsyad Wonosari - Muhammad Idza Adzan Ponulele; Muhammad Yusuf Mahmud Faizullah; Heni Tri Astuti (IIQ An Nur Yogyakarta, 2023)
This research aimed to present the dynamics of the Sekaten tradition in Yogyakarta from the perspective of millennial students at Darul Qur'an Islamic Boarding School, Wal Irsyad, Wonosari, Gunungkidul. This research method was descriptive-qualitative research. Data collection was taken from observation, interviews, and documentation. The research results showed that many millennial generation students in Darul Qur'an Wal Ersyad know the sekaten tradition, but did not know it the basics. It was because they were not originally from Yogyakarta and had never participated in celebrating the Sekaten tradition since childhood. The history of the sekaten tradition was carried out to commemorate the birth of the Prophet Muhammad, so every year this tradition continued to be held in Yogyakarta.